People's century - Pagnamenta, Peter (London : BBC World Wide [production company] ; Kuala Lumpur : Vision Four Home Video [distributor], 1997)
Through fascinating eyewitness accounts this acclaimed series examines how political, economic and technological changes transformed the lives of ordinary people
episode 1. 1900 Age of Hope - episode 2. 1914 Killing fields - episode 3. 1917 Red Flag - episode 4. 1919 Lost peace - episode 5. 1924 On the line - episode 6. 1927 Great escape - episode 7. 1929 Breadline - episode 8. 1930 Sporting fever - episode 9. 1933 Master race - episode 10. 1939 Total war - episode 11. 1945 Fall out - episode 12. 1945 Brave new world - episode 13. 1947 Freedom now - episode 14. 1948 Boom town - episode 15. 1949 Great leap - episode 16. 1951 Asia rising - episode 17. 1954 Living longer - episode 18. 1957 Skin deep [episode 19-21 are not available] - episode 22. 1970 Half the people - episode 23. 1975 War of the flea - episode 24. 1979 God fights back - episode 25. 1989 People power - episode 26. 1997 Fast forward
Copy available in DVD format
Narrator: Sean Barrett, Veronika Hyks
Keywords: United Kingdom -- History -- 20th century; United Kingdom -- 20th century; United Kingdom -- Economic conditions -- 20th century; United Kingdom -- Politics and government -- 20th century